Study of food security and its related factors in Iranian families referred to health centers in Qazvin - Siahipour, Sonia; Khodabakhshi, Adeleh; Mehrad-Majd, Hassan; Noroozi, Mostafa; Moghadam, Seyed Amir Hossein Zehni (Progress in Nutrition, 2019)
Food insecurity is defined as limited access to nutritionally sufficient and safe foods to meet dietary needs for a healthy life. Over decades, several factors including food insecurity has led to rise on global hunger and malnutrition. The present study was aimed to investigate the prevalence of food insecurity and its related factors in the families supported by healthcare centers and health posts in Qazvin. All mothers referred to health centers in Qazvin during the year 2015, were entered in this descriptive and analytical survey. Two sets of survey questionnaires, the Food Security Questionnaire of U.S. Department of Agriculture (USDA) and Basic Family Information Questionnaire, were applied for data collection. Chi square test were applied for statistical analysis. The total prevalence of food insecurity among the families of studied population was 68.8%; comprised 41.4% without hunger, 21.7% with moderate hunger, and 5.7% with severe hunger. Eighty one percent of participants were housewives, otherwise the other were working mothers. A meaningful relationship was found between food security and some parental features including education, job, age, family size, monthly family income, and the settlement status. In conclusion our results indicated a high prevalence of food insecurity among families in Qazvin city. Effective prevention strategies and practical approaches by corresponding organizations are necessary to promote nutritional awareness of families to prevent food insecurity.